Reducing Sulfur Emissions: Logistical and Environmental Considerations - Zis, Thalis; Psaraftis, Harilaos N. (My University, 2019)
In recent years the issue of sulfur emissions from maritime transport has seen newfound attention. This chapter presents an overview of the main issues of sulfur emissions and the legislative framework that seeks to reduce the sulfur footprint of the maritime sector. It also analyzes potential modal shifts toward less efficient land-based modes which may happen as a result of sulfur regulations and investigates the related potential economic damage to ship operators. To that effect, this chapter presents findings from a recently finished project at DTU and the developed methodological framework that can be used to estimate such modal shifts, as well as to measure the efficacy of policy and ship operators’ measures to reverse such shifts.
Keywords: Sulfur emissions; Legislative framework